2023
DOI: 10.1007/s43545-023-00608-8
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in academic performance of students studying Science Technology Engineering and Mathematics (STEM) subjects at the University of Ghana

Abstract: Using a mixed-methods research design, this study compares academic performance of males and females studying STEM subjects or courses at the university level with that of the senior high school level performance. The factors contributing to the gender differences in academic performance at the two levels of the educational ladder were also explored. Overall, the results show that the academic performance of males was better than females at the senior high school level, whilst at the tertiary level, the academ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 41 publications
2
9
0
2
Order By: Relevance
“…On the contrary, females have shown superior performance in multiple mathematics-related courses compared to males. Wrigley-Asante et al (2023) conducted a comparative study between college students' performance in STEM subjects in Advanced Placement (AP) exams and their high school subject grades. They found that male students had better AP scores during their high school years.…”
Section: Discussion Of Differential Analysis Resultsmentioning
confidence: 99%
“…On the contrary, females have shown superior performance in multiple mathematics-related courses compared to males. Wrigley-Asante et al (2023) conducted a comparative study between college students' performance in STEM subjects in Advanced Placement (AP) exams and their high school subject grades. They found that male students had better AP scores during their high school years.…”
Section: Discussion Of Differential Analysis Resultsmentioning
confidence: 99%
“…Regarding AS, studies have examined how technology integration can foster students’ dedication, responsibility, and commitment to their academic tasks [ 51 ]. [ 52 ] conducted a study that integrated technology into the English classroom and found that it enhanced students’ sense of responsibility and self-directed learning. They observed that students took ownership of their learning process and were motivated to complete tasks independently.…”
Section: Review Of Literaturementioning
confidence: 99%
“…AS is a psychological concept that stems from an intrinsic eagerness that can also be referred to as AE [ 52 ]. AS is a skill that empowers individuals to establish specific objectives and subsequently attain them.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Variations in subject choice for one or both majors in STEM education result when teachers feel underprepared to teach science (Fitzgerald & Smith, 2016). Even though it is imperative to continue encouraging females to study STEM fields and pursue STEM careers, it is equally important to develop policy measures to address males' performance at the tertiary level (Wrigley-Asante et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%